Bridging the Research—Practice Gap in Nepalese Business Schools - Ojha, Gaurav (SAIM Journal of Social Science and Technology, 2025)
Purpose: This study investigates the research-practice gap in Nepalese management education, focusing on how business schools in Kathmandu Valley create and share knowledge. It aims to identify factors contributing to this gap in their research methods and dissemination. Research Methodology: A cross-sectional survey was conducted with 80 business educators from graduate and postgraduate programs in Kathmandu Valley. Participants involved in teaching, publishing, or managing research completed questionnaires addressing factors affecting the research-practice divide in knowledge activities. Findings: Key contributors to the research-practice gap include self-referential practices, subjective norms, weak corporate networks, and communication issues, with self-referential tendencies highlighted as the primary factor by educators. Implications: Nepalese business schools should move beyond internally focused academic practices and actively leverage their research knowledge in collaborative, professional, and practical contexts to bridge the gap and improve management education’s impact. Originality/Value: Offering empirical insights into the antecedents of the research-practice gap within Kathmandu Valley business schools, this study presents a context-specific framework to help align academic research with practical application in emerging markets.